Adequacy of Nutritional Support and Reasons for Underfeeding in Neurosurgical Intensive Care Unit Patients - Hwasoon Kim, RN, PhD; Jeong Ae Shin, RN, MSN; Jae Youn Shin, RN, BSN; Ok Min Cho, RN, BSN (Elsevier, 2010)
The purpose of the study was to identify the adequacy of enteral feeding, and the reason and prevalence of under-nutrition, and to determine the relationships between caloric intake and resulting nutritional parameters among neurosurgical intensive care unit (ICU) patients. Methods: The participants for this descriptive study were 47 neurosurgical ICU patients who had enteral feeding initiated after ICU admission. Data were collected from the initial day of enteral feeding for 7 days. Data related to enteral feeding, feeding interruptions or delay, prealbumin, and transferrin were collected. Results: The mean age of the participants was 56.62 years. Twenty-six patients did not receive their feeding formula more than once during 7 days, and 11 had interruptions more than 6 times. The mean number of feeding interruptions was 3.23 (SD = 4.47). On the average, only 76.44% of the estimated energy requirement was provided by enteral feeding to the patients. The frequency of underfeeding was 52.17% with respect to enteral feeding. The most frequent reason for the feeding interruption was observation before and after intubation and extubation, which was unavoidable. The next most common reason was gastrointestinal bleeding, mostly due to old clots or trace, followed by residual volume less than 100 mL. Changes in prealbumin and transferrin levels for 7 days between the underfed and adequately fed groups were not statistically significant. Conclusion: The management of enteral feeding by nurses was overprotective because of the unpredictable nature of ICU patients in terms of their underlying disease process. The management of feeding intolerance needs to be evidence-based and nurses must consistently follow the protocol that has been supported as a useful measure.